Indian Constitution and Social Transformation: Exploring the Role of the Indian Constitution in Social Progress (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Constitution of a country is the highest legal-political document for its government. It also embodies the statement of rights of the people as lawfully established. In a general sense it lays down the structure of power and obligations of the rulers towards the ruled. Such obligations imply not only the limit of the governmental power but also the expectation of the people from the government. A significant point about a Constitution is that it is future oriented, rather than past oriented. People who administer their affairs according to traditions and customs do not need a constitution. The memories of their elders are sufficient for them. Historically, whenever a Constitution has been framed, it has followed a revolution. A Constitution has been intended to usher in a new social and political order. In the Eighteenth century, when the first written constitution in the world appeared – in the United States of America – only the bare structure of a federal republican government was laid down in 1789. That was a break with the monarchical colonial links with Britain. Within two years, the Constitution of the United States went through ten amendments incorporating the rights of the people in the form of limits to governmental power. The assumption was that the people had certain rights, naturally, and the Government could not take them away. Those rights were conceived in terms of the liberal laissez faire doctrine that put premium on the rights to life, liberty and personal property. The Constitution of every nation is the Supreme Law and only this can deliver justice to all with maintaining equality and upholding the rights of Natural Justice.